Аналіз результатів моделювання роботи прикордонної станції при використанні різних технологічних рішень зміни міжколійної відстані - Обухова, А. Л. (Eastern-European Journal of Enterprise Technologies, 2009)
In article the pressing questions connected with reducing of time of a finding of rail cars at frontier stations, namely between the states which have different width of a track are considered. It is offered to model on the basis of networks of Petri which display schedules of handling of trains at station at use of different technological decisions of change of distance between wheel steams and give the chance to estimate merits and demerits, and also to track ”narrow” places at use of each of the considered ways